An Analysis of the Quality of Ph.D Theses: A Peep Through In-text Citations And Bibliography - Unnikrishnan S
This study attempts to analyze the quality of Ph.D theses awarded by Mahatma Gandhi University, South India in the field of Social Sciences through their in-text citations and bibliography. This is done by foregrounding the mistakes made by the scholars in their theses. In between 2017-18, the university had awarded 69 Ph.Ds under Social Sciences of which 25 theses were selected for this study. The major finding of the study is that even though American Psychological Association (APA) style of citation is generally accepted across the academic community, none follow it strictly. This is because research guides are often permitted to make their own changes in the style sheets. As no criteria was framed with regards the information sources that might be used as reference sources, even local newspapers were used by the researchers. The internet facility was used by all researchers but often failed its meaningful representation in their bibliography. 13 theses provided chapter reference in addition to their bibliography thus making the thesis bulky. In 12 theses the bibliography was broken down under subheads such as Books, Journals etc., of which 7 had no chapter references, making it difficult for the evaluators to find out the details of in-text citations. The overall observation made is that both the research guides as well as scholars are either unaware of the role of existing literature over research or not giving due importance to its presentation. Suggestions to improve the present scenario and possible solutions are discussed herewith.